Systematic identification of phosphorylation-mediated protein interaction switches - Betts, Matthew J.; Wichmann, Oliver; Utz, Mathias; André, Timon; Gavin, Anne-Claude; Bork, Peer; Russell, Robert B. (PLoS Computational Biology, 2017)
Proteomics techniques can identify thousands of phosphorylation sites in a single experiment, the majority of which are new and lack precise information about function or molecular mechanism. Here we present a fast method to predict potential phosphorylation switches by mapping phosphorylation sites to protein-protein interactions of known structure and analysing the properties of the protein interface. We predict 1024 sites that could potentially enable or disable particular interactions. We tested a selection of these switches and showed that phosphomimetic mutations indeed affect interactions. We estimate that there are likely thousands of phosphorylation mediated switches yet to be uncovered, even among existing phosphorylation datasets. The results suggest that phosphorylation sites on globular, as distinct from disordered, parts of the proteome frequently function as switches, which might be one of the ancient roles for kinase phosphorylation.
Published: March 27, 2017
Gesehen am 12.06.2018